2009
DOI: 10.1002/ptr.2716
|View full text |Cite
|
Sign up to set email alerts
|

A furanquinone from Paulownia tomentosa stem for a new cathepsin K inhibitor

Abstract: In the search for novel inhibitors of cathepsin K, a new furanquinone compound, methyl 5-hydroxy-dinaphtho[1,2-2'3']furan-7,12-dione-6-carboxylate (1a), showed in vitro inhibitory activities for cathepsin K. Compound 1a was isolated originally from Paulownia tomentosa stem and its derivatives were synthesized. Furanquinone compounds (1a, 1b, 1c and 1d) were also found to be capable of inhibiting cathepsin L, which is closely related to cathepsin K. The inhibitory activity of the parent compound 1a (IC50 = 21 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…5). This decrease in T C is in agreement with the reported literature on rare earth ion doping in BaTiO 3 [15,20,29]. The frequency of low transverse-optic mode of the vibration can be expressed as…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…5). This decrease in T C is in agreement with the reported literature on rare earth ion doping in BaTiO 3 [15,20,29]. The frequency of low transverse-optic mode of the vibration can be expressed as…”
Section: Resultssupporting
confidence: 90%
“…However, most of these studies are limited to site occupancy in BaTiO 3 and information on the influence of rare earth ion substitution on the microstructure and dielectric behaviour is limited. Park et al [15] discussed the influence of grain size and external pressure on the dielectric transition temperatures in Gd 3+ doped BaTiO 3 . Investigations of the effects of rare earth ion substitution on site occupancy, microstructure and dielectric properties of Ba(Zr,Ti)O 3 ceramics began recently.…”
Section: Introductionmentioning
confidence: 99%
“…Smejkal et al isolated several compounds from P. tomentosa (Smejkal et al, 2007a(Smejkal et al, , 2007b(Smejkal et al, , 2008a(Smejkal et al, , 2008b(Smejkal et al, , 2010. Park et al reported on the use of a furanquinone isolated from the stem of P. tomentosa as a new cathepsin K inhibitor (Park et al, 2009). Although some natural compounds have been isolated from P. tomentosa, their biological activities have not been fully characterized.…”
Section: Introductionmentioning
confidence: 97%
“…It has been used traditionally to treat cough, phlegm, bronchitis, asthma, hemorrhoid, gonorrhea, and erysipelas. 1) Previous phytochemical studies of the genus Paulownia have reported the isolation of iridoids, 2,3) lignans, 4) furanoquinones, 5) phenolic glycosides, 6) and flavonoids. 7,8) Recently, geranylated flavonoids isolated from the genus Paulownia have been reported to possess a series of bioactivities including antiviral, 9) antioxidant, 10) antimicrobial, 11) cytotoxic, 12) and anti-cholinesterase activities.…”
mentioning
confidence: 99%
“…In our continuing search for the plant-derived inhibitors of nitric oxide (NO) production, the methanolic extract of P. coreana was found to inhibit the lipopolysaccharide (LPS)-induced NO production in RAW264.7 cells. Subsequent bioassay-guided fractionation of the CH 2 Cl 2 -soluble fraction led to the isolation of a new geranylated flavanone, 3′-O-methyl-5′-hydroxydiplacol (1), together with 10 known compounds (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). The structures of known isolates were elucidated on the basis of their spectroscopic analysis ( 1 H-, 13 C-NMR, and electrospray ionization (ESI)-MS) by comparison with those of published data.…”
mentioning
confidence: 99%